2006
DOI: 10.1093/jac/dkl076
|View full text |Cite
|
Sign up to set email alerts
|

Failure to implement hospital antimicrobial prescribing guidelines: a comparison of two UK academic centres

Abstract: This study highlights inadequacies in the implementation and promotion of local guidelines, and demonstrates the potential for widely varying antimicrobial practices in two comparable UK cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 9 publications
1
33
0
2
Order By: Relevance
“…In the present study, the fact that it was conducted in a university hospital can explain providers' high adherence to the protocol because it is a setting where the focus is on prescribers' training. The same was reported by Ali et al, 1 who showed that the most important infl uence for prescription choice in medical schools was teachers and senior doctors' guidance.…”
Section: Resultssupporting
confidence: 75%
“…In the present study, the fact that it was conducted in a university hospital can explain providers' high adherence to the protocol because it is a setting where the focus is on prescribers' training. The same was reported by Ali et al, 1 who showed that the most important infl uence for prescription choice in medical schools was teachers and senior doctors' guidance.…”
Section: Resultssupporting
confidence: 75%
“…In other words, as guided by our data, we recognise that these factors will always limit prescribing decisions and place more emphasis on solutions that can work in the face of uncertainty, inexperience and lack of knowledge. For the same reasons, our analysis draws less attention to uncertainty about technical aspects of the process of prescribing, [56][57][58][59] poor dissemination of information or conflicting guidelines and lack of awareness, 43,[60][61][62][63][64][65] and operational inefficiencies and pressures. 43,62,[66][67][68][69][70] Instead, we are looking to understand what drives the behaviour of doctors in training in the presence of these limitations -namely uncertainty, inexperience and lack of knowledge.…”
Section: Chapter 3 Findingsmentioning
confidence: 99%
“…The educational role of pharmacists 43,60,64,125,171,181 and infectious disease specialists 102 has been extensively discussed in the literature as critical for appropriate antimicrobial prescribing. Accepting antimicrobial prescribing more widely as 'a specialised act' 102 could significantly legitimise the input of antimicrobial specialists and contribute to their meaningful involvement.…”
Section: Input From Other Professional Groupsmentioning
confidence: 99%
See 2 more Smart Citations